2014
DOI: 10.3109/15563650.2014.925562
|View full text |Cite
|
Sign up to set email alerts
|

‘Crazy Monkey’ Poisons Man and Dog: Human and canine seizures due to PB-22, a novel synthetic cannabinoid

Abstract: We present a laboratory-confirmed case report of human and canine neurotoxicity associated with a novel synthetic cannabinoid, PB-22 (QUIPIC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 11 publications
7
32
0
Order By: Relevance
“…hippocampus, amygdala and cortex) thus favoring the onset of convulsions (Vilela et al, 2013). These preclinical data are in agreement with the increasing clinical reports showing the occurrence of seizures and hyperreflexia in young people who have smoked ''spice'' products containing different synthetic cannabinoids (Lapoint et al, 2011;Simmons et al, 2011;Schneir and Baumbacher, 2012;McQuade et al, 2013;Gugelmann et al, 2014) and clearly outline that these compounds are extremely dangerous to human health.…”
Section: But Inhibits Visual and Acoustic Sensorimotor Responsessupporting
confidence: 83%
“…hippocampus, amygdala and cortex) thus favoring the onset of convulsions (Vilela et al, 2013). These preclinical data are in agreement with the increasing clinical reports showing the occurrence of seizures and hyperreflexia in young people who have smoked ''spice'' products containing different synthetic cannabinoids (Lapoint et al, 2011;Simmons et al, 2011;Schneir and Baumbacher, 2012;McQuade et al, 2013;Gugelmann et al, 2014) and clearly outline that these compounds are extremely dangerous to human health.…”
Section: But Inhibits Visual and Acoustic Sensorimotor Responsessupporting
confidence: 83%
“…Exposure to PB-22 containing product "Crazy Monkey" (see Fig. 1) lead to seizures in a man and his dog; laboratory analysis of human and canine plasma revealed the presence of PB-22 (Gugelmann et al, 2014). PB-22 was suspected to be involved in three deaths in Australia (Gerostamoulos et al, 2015).…”
Section: Synthetic Cannabimimetics (Scs)mentioning
confidence: 97%
“…Four of the six compounds (UR-144, XLR-11, AKB-48, and AB-FUBINACA) have been identified in samples of synthetic cannabinoids obtained on the street (Kavanagh et al, 2013; Uchiyama et al, 2013; Strano Rossi et al, 2014). All six of the compounds have been found in blood or urine samples (or identified by verbal report) of users reporting adverse effects (Behonick et al, 2014; Gugelmann et al, 2014; Mohr et al, 2014; Strano Rossi et al, 2014), and the use of UR-144 or XLR-11 has been reported in cases of driving under the influence (Lemos, 2014; Musshoff et al, 2014). Of further concern, several of these compounds have been reported to produce significant adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Of further concern, several of these compounds have been reported to produce significant adverse effects. For example, PB-22 caused convulsions in humans and canines (Gugelmann et al, 2014) and 5F-PB-22 was present in three cases of sudden death (Behonick et al, 2014). Renal toxicity associated with the use of synthetic cannabinoids has also been reported, with XLR-11 being identified in several of the cases (Centers for Disease Control and Prevention, 2013; Buser et al, 2014).…”
Section: Introductionmentioning
confidence: 99%